RNA‐Seq Highlights High Clonal Variation in Monoclonal Antibody Producing CHO Cells. Issue 3 (1st February 2018) - Orellana, Camila A.; Marcellin, Esteban; Palfreyman, Robin W.; Munro, Trent P.; Gray, Peter P.; Nielsen, Lars K.
Abstract : The development of next‐generation sequencing technologies has opened new opportunities to better characterize complex eukaryotic cells. Chinese hamster ovary (CHO) cells play a primary role in therapeutic protein production, with currently five of the top ten blockbuster drugs produced in CHO. However, engineering superior CHO cells with improved production features has had limited success to date and cell lines are still developed through the generation and screening of large strain pools. Here, we applied RNA sequencing to contrast a high and a low monoclonal antibody producing cell line. Rigorous experimental design achieved high reproducibility between biological replicates, remarkably reducing variation to less than 10%. More than 14 000 gene‐transcripts are identified and surprisingly 58% are classified as differentially expressed, including 2900 with a fold change higher than 1.5. The largest differences are found for gene‐transcripts belonging to regulation of apoptosis, cell death, and protein intracellular transport GO term classifications, which are found to be significantly enriched in the high producing cell line. RNA sequencing is also performed on subclones, where down‐regulation of genes encoding secreted glycoproteins is found to be the most significant change. The large number of significant differences even between subclones challenges the notion of identifying and manipulating a few key genes to generate high production CHO cell lines. Abstract : CHO cells are widely used for biopharmaceutical production. In this study, the authors applied RNA sequencing to contrast high and low monoclonal antibody producing cell lines. A large number of significant differences even between subclones is observed and challenges the notion of identifying and manipulating a few key genes to generate high production cell lines.